ANALISIS KESULITAN GURU DALAM PEMBELAJARAN TEMATIK - Dwi Ramadani Prastianingsih; Berchah Piteoewas; hermi Yanzi (Jurnal Kultur Demokrasi, 2012)
The purpose of this study to explain the difficulties teachers in implementing the thematic learning in the classroom and then provide a solution to the teachers, especially in elementary school 3 Haji Pemanggilan to implement thematic learning in classes I-III. This research uses descriptive method, the research subjects all teacher in elementary school state 3 Haji Pemanggilan.Techniques of data collection using a questionnaire and analyzed using percentage techniques. The results showed that; on indicator of knowledge factor they know but do not understand the concept of thematic learning and its sub-indicators, it is shown by the percentage of 80% of respondents.By 10% of respondents already and understand the concept of thematic learning, and 10% of respondents lack knowledge and understanding about the concept of thematic learning.Then on indicator of interest and willingness factor is as much as 60% of respondents have an interest and willingness in the medium category, and even 30% of respondents can be said to have a low interest and willingness, and only 10% of respondents who have a high interest and willingness.In addition, the indicators of carrying capacity is as much as 40% of respondents said that the carrying capacity of the thematic learning has not been adequate in the several themes of learning, even 50% of respondents said that the carrying capacity of the thematic learning is inadequate and only 10% of respondents who said that the carrying capacity in thematic learning was adequate. Based on the research concluded that the respondent had difficulty in the implementation of thematic learning as influenced by several factors, such as knowledge about the concept of thematic learning, low interest and willingness to understand the concept of thematic learning, inadequate carrying capacity, and socialization are less of education office.